Test Of Exchange Market Efficiency In Nigeria - Oloyede, John Adebayo; Otapo, Toyin Waliu (Advances in Social Sciences Research Journal, 2018)
This study investigated the foreign exchange market in Nigeria to determine the significance of past exchange rates in predicting the present exchange rates which is a test of weak form efficiency. It examined the cointegration and causal relationships between selected pairs of exchange rates to determine the semi strong form efficiency, and inspected the variant of the Random Walk Model that exchange rates in Nigeria conformed to. Secondary data sourced mainly from the Central Bank of Nigeria Statistical Bulletin 2014 and its official websites were used. The study’s data were the spot and nominal monthly average foreign exchange rate series from the official market of Naira to Dollar, Naira to Pounds, Naira to Yen, Naira to Swiss Franc and Naira to CFA Franc between January, 1986 and December, 2015. Methods used include the autocorrellation function, unit root tests, Johansen Cointegration and Granger Causality tests. Autocorrelation and unit root tests revealed that all the series were non-stationary at level and became stationary at first difference. In addition, the Johansen cointegration test revealed that there were no cointegrating equations between selected pairs of exchange rates. The Granger causality test supported no causal relationship between selected pairs of exchange rates and the coefficients of determination were highest with the assumption of intercept and trend. The findings implied that the foreign exchange market in Nigeria within the sample period was efficient in the weak and semi strong forms, that is, information in past exchange rate series and public information were fully reflected in current exchange rates, the exchange rate series lacked exploitable pattern and conformed to the Random Walk Model with intercept and deterministic trend. The study therefore recommended that a more liberalized flexible exchange rate regime and improvements in money supply, national income, local and foreign bonds.